Lingucultural Study Of Linguistic Gradation In Works Translated Into English And Uzbek (Global Scientific Review, 2024)
It is good to transliterate the subject names and terms related to the ethnic origin, customs and traditions of the nations and add brief explanation notes in the translation. Within the framework of current linguo-cultural studies, it has become a trend to conduct research on translations of works that are considered cultural property, because through translation, it opens a great way for the expansion of intercultural communication between many countries. "Bygone Days" written by Abdulla Qadiri, one of the classic Uzbek works is one of the tasks entrusted to the translator to study the prose works of national literature from the linguistic and cultural point of view, to preserve the traditions and experiences of the people in the translation of the work, because we think that being able to vividly express the translation of the work can be a basis for studying the national colorful history of that nation for the new reader